Role of full-time union officer - Robertson, N.Sams, K.I. (Economic & Social Studies, 1976)
Many commentators on industrial relations postulate a more ambitious and elaborate role for the trade unions. Leading figures within the movement itself hold similar views. Such developments might be expected to place additional burdens on the professional administrators o f unions, the full-time officers. Yet the full-time officer has been a relatively neglected figure in the study of industrial relations. The main purpose of the present study has been to investigate the role of the full-time officer, and the extent to which his capacities seem suited to that role both now and as it may develop. It will be argued that the nature o f the job and the personal characteristics of the officer have increasingly diverged. The consequences for the organisation and administration of unions, and for public policy relating to industrial relations, are explored.
Keywords: Trade Union; Industrial Relations